The OCLC Research Survey of Special Collections and Archives - Dooley, Jackie M. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
This paper summarizes the outcomes of the 2009 OCLC Research survey of 275 research libraries in the United States and Canada regarding the current status of their special collections and archives. The resulting report, Taking Our Pulse: The OCLC Research Survey of Special Collections and Archives, includes detailed analysis of the data and thirteen recommendations for community action. The three most common challenges named by respondents were space, digitization, and born-digital materials. Collections are growing dramatically, use of all types of material has increased, substantial backlogs remain, and 75% of library budgets have been reduced in recent years.